UNDERSTANDING THE QUR’AN AND HADITH RELATED TO CHILDREN'S DEVOTION TO PARENTS WITH HERMENEUTICS OF TAWHID - Hadiyansyah, Dhuha; In'ami, Moh; Hunaida, Wiwin Luqna; Anasy, Zaharil; Faizah, Umi (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
children and parents. Thus far, these two sacred texts have been used as the basis for a children’s obedience to their parents. In this sense, being obedient to both parents, whether the ordered is obligatory, sunnah or permissible, is a must. Likewise, if parents forbid from unlawful, makruh or permissible actions, the children are obliged to obey. In this view, obedience to parents is absolute; there is no concept of self-boundary, which in psychology is valued as an important component in the growth of a healthy identity. The study found that, by using Hermeneutics of Tawhid, the interpretation of the two texts becomes more fair, namely the form of obedience of children to their parents lies in the obedience to roles and functions in the family system. When parents act as caregivers in the family, children need to obey them as the owner of the authority; conversely, when the caregiver role changes, parents need to adjust to the new situation. Through this interpretation, the parent-child relationship pattern can be seen as a bond capable of supporting the sakinah family concept. Wadud's Hermeneutics of Tawhid gives us the opportunity to read texts with a broad horizon of thinking in order to produce more acceptable meanings for those who think logically. This meaning would be more functional to be applied in everyday life in society, not the meaning that only exists in the world of ideas.[Artikel ini merupakan penelitian kualitatif dengan kajian teks, yang fokus pada Surat al-Isra ayat 23 dan Hadits tentang hubungan antara anak dan orang tua. Sejauh ini, kedua teks suci ini telah digunakan sebagai dasar untuk kepatuhan anak-anak kepada orang tua mereka. Dalam pengertian ini, patuh kepada kedua orang tua, apakah perintah itu wajib, sunnah atau diizinkan, adalah suatu keharusan. Demikian juga jika orang tua melarang perbuatan melawan hukum, makruh atau perbuatan yang diizinkan, maka anak-anak wajib taat. Dalam pandangan ini, kepatuhan kepada orang tua adalah mutlak; Tidak ada konsep batas diri, yang dalam psikologi dinilai sebagai komponen penting dalam pertumbuhan identitas yang sehat. Penelitian menemukan bahwa, dengan menggunakan Hermeneutika Tauhid, interpretasi terhadap dua text tersebut menjadi lebih adil, yaitu bentuk ketaatan anak kepada orang tuanya terletak pada ketaatan terhadap peran dan fungsi dalam sistem keluarga. Ketika orang tua bertindak sebagai pengasuh dalam keluarga, anak-anak perlu mematuhinya sebagai pemegang otoritas; sebaliknya, ketika peran pengasuh berubah, orang tua perlu menyesuaikan diri dengan situasi baru. Melalui interpretasi ini, pola hubungan orangtua-anak dapat dilihat sebagai ikatan yang mampu mendukung konsep keluarga sakinah. Hermeneutika Tauhid Wadud memberi kita kesempatan untuk membaca teks dengan cakrawala berpikir yang luas demi menghasilkan makna yang lebih berterima oleh mereka orang yang berpikir logis. Makna ini lebih fungsional untuk diterapkan dalam kehidupan sehari-hari di masyarakat, bukan makna yang hanya ada di dunia ide.]